2006
DOI: 10.1634/theoncologist.11-2-126
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic Differences in Genetic Polymorphisms of CYP2D6 in the U.S. Population: Clinical Implications

Abstract: After completing this course, the reader will be able to:1. List the four different genotypes for CYP2D6 polymorphism.2. Understand the potential effects of CYP2D6 polymorphism on the efficacy and safety for drugs metabolized via this enzyme.3. List the ethnic groups that are most frequently affected by genetic variation of the CYP2D6 enzyme. Access and take the CME test online and receive 1 AMA PRA category 1 credit at CME.TheOncologist.com CME CME This material is protected by U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
1
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(188 citation statements)
references
References 64 publications
7
168
1
11
Order By: Relevance
“…Pertinent to the current discussion of tamoxifen metabolism, the CYP2D6*4 allele [130] is estimated to have a frequency of 12-23% in Causasians, 1.2-7% in black Africans and 0-2.8% in Asians [127,128]. A lower estimate of (<10%) of the PM phenotype is presented by Bernard and coworkers [131].…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%
“…Pertinent to the current discussion of tamoxifen metabolism, the CYP2D6*4 allele [130] is estimated to have a frequency of 12-23% in Causasians, 1.2-7% in black Africans and 0-2.8% in Asians [127,128]. A lower estimate of (<10%) of the PM phenotype is presented by Bernard and coworkers [131].…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%
“…The 291 allele *10 was detected with a prevalence of 16,5%, which is higher than the expected 292 based on large European population studies and according to CYP2D6 Allelic Variation 293 Summary Table in http://www.cypalleles.ki.se/cyp2d6.htm [30,31] but is in accordance 294 with a recent study for Portuguese population [32]. CYP2D6*10 isn't a null allele but it 295 can decrease the enzymatic activity and change the substrate specificity of the enzyme 296 [13,[33][34][35].…”
mentioning
confidence: 67%
“…The selection of variants should be partially based on the patient population which the laboratory serves; studies have revealed that specific SNPs within germline drug metabolizing genes can be prominent within specific ethnic groups [129]. For example, CYP3A5 is expressed only in approximately 10% of the European population [130].…”
Section: Criteria For Selecting a Genotyping Methodsmentioning
confidence: 99%